2018
DOI: 10.2196/jmir.8667
|View full text |Cite
|
Sign up to set email alerts
|

Evidence From Web-Based Dietary Search Patterns to the Role of B12 Deficiency in Non-Specific Chronic Pain: A Large-Scale Observational Study

Abstract: BackgroundProfound vitamin B12 deficiency is a known cause of disease, but the role of low or intermediate levels of B12 in the development of neuropathy and other neuropsychiatric symptoms, as well as the relationship between eating meat and B12 levels, is unclear.ObjectiveThe objective of our study was to investigate the role of low or intermediate levels of B12 in the development of neuropathy and other neuropsychiatric symptoms.MethodsWe used food-related Internet search patterns from a sample of 8.5 milli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Indeed, the vast majority of Internet users refer to search engines when they have a medical concern [4]. For this reason, search queries have been used to track infectious diseases such as influenza [10,7], answer questions on the relationship between diet and chronic pain [5], and to identify precursors to disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the vast majority of Internet users refer to search engines when they have a medical concern [4]. For this reason, search queries have been used to track infectious diseases such as influenza [10,7], answer questions on the relationship between diet and chronic pain [5], and to identify precursors to disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…The richness of search engine queries, reflecting a broad range of human behaviors, has led researchers analyze these data to learn about aspects of health which are difficult to study in other ways [19]. These studies begun from an examination of broad aspects of public health, e.g., the prevalence of influenza in a population [11] and the effect of dietary deficiencies on certain chronic pains [3]. More intriguingly, recent work has demonstrated that insights pertaining to individuals can be found their queries.…”
Section: Introductionmentioning
confidence: 99%
“…Recipe searches provide a representative sample of the dietary consumption of individuals [18]. Therefore, to evaluate the changes in diet made by people with CRQs, we followed the methodology used previously [18] to identify queries for recipes and map them to ingredients therein.…”
Section: Methodsmentioning
confidence: 99%